Central bank communication on fiscal policy - Julien Allard; Marco Catenaro; Jean-Pierre Vidal; Guido Wolswijk (European Central Bank (ECB), 2012)
While the established literature on central bank communication has traditionally dealt with communication of monetary policy messages to financial markets and the wider public, central bank communication on fiscal policy has so far received little attention. This paper empirically reviews the intensity of central banks' fiscal communication by five central banks (the US Federal Reserve, the ECB, the Bank of Japan, the Bank of England and the Swedish Riksbank) over the period 1999-2011. To that end, it develops a fiscal indicator measuring the fiscal-related communication in minutes or introductory statements. Our findings indicate that the ECB communicates intensively on fiscal policies in both positive as well as normative terms. Other central banks more typically refer to fiscal policy when describing foreign developments relevant to domestic macroeconomic developments, when using fiscal policy as input to forecasts, or when referring to the use of government debt instruments in monetary policy operations. The empirical analysis also indicates that the financial crisis has overall increased the intensity of central bank communication on fiscal policy. It identifies the evolution of the government deficit ratio as a driver of the intensity of fiscal communication by central banks in the euro area, the US and Japan, and for Sweden since the start of the crisis. In England the fiscal share in central bank communication is related to developments in government debt as of the start of the crisis.
Keywords: E58; E61; E63; 330; central bank communication; Fiscal Policy; quantification of verbal information